A Description of English Teaching Based on Curriculum Merdeka - Hikmawati, Hikmawati; Nurwati, Andi; Kadir Ismail, Abdul (ELOQUENCE : Journal of Foreign Language, 2024)
Background: The curriculum change from the 2013 Curriculum to the Merdeka Curriculum has brought changes to the teaching process of a subject, including the English subject. Purpose: This research aims to describe the teaching of English based on the Merdeka curriculum at SMK Negeri 1 Limboto. Method: This research aims to describe the teaching of English based on the Merdeka curriculum at SMK Negeri 1 Limboto. Results and Discussion: The results of the research showed that during four observation sessions, the teacher consistently carried out all core learning activities stages as outlined in the observation guide. Similarly, students demonstrated active participation in the learning process, including praying, answering stimulus questions, identifying expressions from the discussed topics, working in groups, completing tasks, discussing, presenting discussion results, and participating in evaluations provided by the teacher. Conclusions and Implications: In conclusion, while the implementation of the Merdeka Curriculum has been undertaken with considerable effort and knowledge, there is still room for improvement in supporting teachers to be better prepared and able to implement this curriculum effectively in their learning processes. while the implementation of the Merdeka Curriculum has been carried out with various preparations and existing knowledge, there is still room for improvement in supporting teachers to be better prepared and able to effectively implement this curriculum in their learning process, especially in terms of in-depth understanding of its characteristics, module preparation, assessment, and adjustment of supporting infrastructure. This that English teaching based on the Merdeka curriculum provides autonom and students in setting goals and the methods to achieve them.